FAKTOR-FAKTOR YANG MEMPENGARUHI HARGA SAHAM PADA PERUSAHAAN PROPERTY DAN REAL ESTATE DI BURSA EFEK - Apriyani, Paula Yoshi; Mardika, Nanda Harry (SCIENTIA JOURNAL, 2020)
The purpose of this study is to determine whether there is a partial influence and influence of DER, ROA and ROE variables on stock prices in property and real estate companies listed on the Indonesia Stock Exchange. The population in this study amounted to 48 companies and then the sampling technique with certain considerations in order to obtain a sample of 32 companies. Data sources using secondary sources in the form of notes or financial statements. The analytical method for testing is done by using SPSS 25 software. The t test results for the Debt To Equity Ratio variable are -1.597 and 1.978 and the significance value is 0.113. The Return On Aseet variable is 5.785 and the table is 1.978 and the significance value is 0.000, and the Return On Equity variable is 3.248 and the table is 1.978 and the significance value is 0.001. It can be concluded that Return On Aseet and Return On Equity have a positive and significant effect on stock prices, while Debt To Equity Ratio does not have a significant effect on stock prices. f test results where the results of fcount of 11.982> ftabel of 2.68 and a significance value of 0,000 so that the results can be concluded for the variable Debt To Equity Ratio, Return On Aseet and Return On Equity together have a significant effect on Stock Prices .